Pengembangan LKS Bermuatan Budaya dalam Adat Melayu Tijak Tanah Ketapang - Sri Nurhajati; Sandie Sandie; Muchtadi Muchtadi (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims to develop a Student Worksheet (LKS) containing cultural elements in the Malay custom of tajak Tanah Ketapang on the material of two-variable linear equation systems in Class VIII B SMP Negeri 02 Muara Pawan Ketapang. This research is development research that uses the borg ang gall model, namely: Potential and problems, data collection, product design, design validation, design revision, initial trials, and product revisions. The data collection technique used in this research is indirect communication techniques and measurement techniques, while the data collection tools used are validation sheets, questionnaires (teacher and student response questionnaires) and tests. The test subjects in this research were 24 students in class VIII B of SMP Negeri 02 Muara Pawan Ketapang. This research produced a validity level of 90% in the very valid category, a practicality level of 94.85% in the very practical category and an effectiveness level of 79,16% in the very effective category